Participatory modelling to enhance social learning, collective action and mobilization among users of the Mafungautsi forest, Zimbabwe - Standa-Gunda, W.; Mutimukuru, T.; Nyirenda, R.; Prabhu, Ravi; Haggith, M.; Vanclay, J.K. (2003)
Participatory modelling can be a useful process to encourage critical examination of livelihood options and foster sustainable natural resource use through enhanced social learning, collective action and mobilization. The broom-grass group in the Mafungautsi forest reserve serves as a case study of the process and outcomes such participatory modelling. Innovative group facilitation methods enhanced participation in the modelling process. The modelling process complements broader efforts to achieve higher levels of adaptive collaborative management.